Pengaruh Motivasi Dan Pengembangan Karir Terhadap Kepuasan Kerja Pada Karyawan (Studi pada PT.JAPFA COMFEED INDONESIA) - Mochammad Fikri Alfandy; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of this research is to describe job satisfaction, motivation and career development and to know the influence of motivation and career development to job satisfaction at PT. Japfa Comfeed Indonesia employees. The method in this research is using quantitative method. The sample of this research is PT. Japfa Comfeed Indonesia employees by using non probability sampling that is purposive sampling, that is counted 62 respondents. Methods in using data using questionnaires. The analysis process used in this research is the multiple regression analysis. The result of this research indicate that simultaneously motivation and career development has positive and significant effect to job satisfaction at PT. Japfa Comfeed Indonesia employees. While partially motivation has positive and significant effect to job satisfaction and career development has positive and significant effect to job satisfaction at PT. Japfa Comfeed Indonesia employee. Keywords : Job Satisfaction, Motivation, Career Development